Investigation of the interaction of natural disperse minerals Ukraine coloring substances from sugar production - Stetsenko, Natalia; Podobiy, Olena; Grabovska, Olena; Miroshnikov, Oleg (My University, 2012)
To improve the quality of sugar should be possible to remove all other substance from the semi-sugar production. Removal of dyeing substances will provide the necessary minimum color of white sugar and its compliance with quality requirements of world standards. Effectiveness removal of dyeing substances from model solutions palygorskite and glauconite depend on pH and subsequently decreasing till at increasing its alkalinity. Investigations to determine the influence of natural disperse minerals in the qualitative indicators of technological solutions of sugar production. The possibility of palygorskite and glauconite for adsorption purification of intermediates.Для підвищення якості цукру повинно бути можливим, щоб видалити всі інші речовини, від напів-цукрового виробництва. Видалення фарбування речовин забезпечить необхідний колір мінімум білого цукру і його відповідність якості вимогам світових стандартів. Ефективність видалення забарвлення речовин з модельних розчинів палигорскіту і глауконіту залежить від рН, а потім зниження до підвищення її лужності. Дослідження з визначення впливу природних дисперсних мінералів в якісних показників технологічних рішень виробництва цукру. Можливість палигорскіту і глауконіту для адсорбційної очищення проміжних продуктів.
Keywords: sugar; dyeing substances; glauconite; adsorbtion; цукор; фарбування речовин; глауконіт; адсорбція; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; кафедра технології цукру і підготовки води; кафедра технології оздоровчих продуктів